Lobbying the Autocrat The Dynamics of Policy Advocacy in Nondemocracies - Grömping, Max; Teets, Jessica C. (Weiser Center for Emerging Democracies, 2023)
Although authoritarian countries often repress independent citizen activity, lobbying by civil society organizations is actually a widespread phenomenon. Using case studies such as China, Russia, Belarus, Cambodia, Malaysia, Montenegro, Turkey, and Zimbabwe, Lobbying the Autocrat shows that citizen advocacy organizations carve out niches in the authoritarian policy process, even influencing policy outcomes. The cases cover a range of autocratic regime types (one-party, multi-party, personalist) on different continents, and encompass different systems of government to explore citizen advocacy ranging from issues such as social welfare, women's rights, election reform, environmental protection, and land rights. They show how civil society has developed adaptive capacities to the changing levels of political repression and built resilience through 'tactful contention' strategies. Thus, within the bounds set by the authoritarian regimes, adaptive lobbying may still bring about localized responsiveness and representation. However, the challenging conditions of authoritarian advocacy systems identified throughout this volume present challenges for both advocates and autocrats alike. The former are pushed by an environment of constant threat and uncertainty into a precarious dance with the dictator: just the right amount of acquiescence and assertiveness, private persuasion and public pressure, and the flexibility to change quickly to suit different situations. An adaptive lobbyist survives and may even thrive in such conditions, while others often face dire consequences. For the autocrat on the other hand, the more they stifle the associational sphere in an effort to prevent mass mobilization, the less they will reap the informational benefits associated with it. This volume synthesizes the findings of the comparative cases to build a framework for understanding how civil society effectively lobbies inside authoritarian countries.